(untitled) (Zaporizhzhia Historical Review, 2021)
The author proves that while separating our own history from the history of our “brethren-neighbors” it is necessary to keep in mind that some facts do not always find understanding even with the indifferent citizens. The controversial character of the problem of positiveness of existence and ideological achievements in the way of founding the country and the nation by the Zaporizhzhia Sich is analysed.